Cerebral Perfusion and Sensory Testing Results Differ in Interstitial Cystitis/Bladder Pain Syndrome Patients with and without Fibromyalgia: A Site-Specific MAPP Network Study - Deutsch, Georg; Deshpande, Hrishikesh; Lai, H Henry; Kutch, Jason J; Ness, Timothy J (Journal of pain research, 2021)
Fibromyalgia is a common co-morbidity in patients with interstitial cystitis/bladder pain syndrome. Quantitative sensory testing measures and regional cerebral blood flow measures have been noted to differ from healthy controls in both subjects with fibromyalgia and those with interstitial cystitis when studied independently. The present study examined such measures in subjects with the diagnosis of interstitial cystitis both with and without the co-diagnosis of fibromyalgia to determine whether differences in these measures may be associated with co-morbidity. Female subjects with the diagnosis of interstitial cystitis with (n = 15) and without (n = 19) the co-diagnosis of fibromyalgia as well as healthy control subjects (n = 41) underwent quantitative sensory testing. A subset of these patients (9 with and 9 without fibromyalgia) underwent brain perfusion studies using arterial spin labeled functional magnetic resonance imaging. An analysis was performed of absolute regional cerebral blood flow of regions-of-interest when experiencing a full bladder compared with an empty bladder. Subjects with both interstitial cystitis and fibromyalgia were more hypersensitive than those without fibromyalgia as well as healthy controls in most sensory measures except heat. Subjects with interstitial cystitis, but no fibromyalgia, differed from healthy controls only in toleration of the ischemic forearm task. Other co-morbidities were more common in those subjects with both interstitial cystitis and fibromyalgia. Bladder fullness was associated with significantly greater whole brain gray matter blood flow in subjects with interstitial cystitis and fibromyalgia when compared with that of subjects with interstitial cystitis without fibromyalgia. Examination of regional cerebral blood flow in individual regions-of-interest demonstrated statistically significant differences between the subjects with interstitial cystitis with and those without fibromyalgia bilaterally in the thalamus, amygdala and hippocampus, as well as the right prefrontal cortex and greater responsiveness to changes in bladder fullness in the insula. Quantitative sensory testing and brain perfusion data support that there are two phenotypes of interstitial cystitis patients, which can be differentiated by a co-diagnosis of fibromyalgia. This may affect responsiveness to treatment and suggest the utility of stratifying interstitial cystitis patients according to their co-morbidities.